Voilà vegan : 85 decadent, secretly plant-based desserts from an American pâtisserie in Paris - Bankert, Amanda (Avery, an imprint of Penguin Random House, 2023)
"100 dessert recipes from a surreptitiously vegan bakery in Paris"--